Pengaruh Metode Pembelajaran Literature Circle terhadap Kemampuan Menulis Teks Ulasan Karya Fiksi di Kelas VIII SMP Muhammadiyah 01 Medan Tahun Ajaran 2025/2026 - Anisa Asari Dewi; Salmah Naelofaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is a quantitative study of the experimental type. The purpose of this study is to determine whether the literature circle learning method has an effect on the ability to write reviews of works of fiction among eighth-grade students at SMP Muhammadiyah 01 Medan. The population used in this study consists of all eighth-grade students at SMP Muhammadiyah 01 Medan, and the sample comprises Class VIII-2 (33 students) and Class VIII-5 (32 students). The sampling technique employed in this study is simple random sampling. The data collection techniques used in this study were observation sheets, documentation, and tests. The results of the ability to write reviews of fictional works in the control class, which used the contextual method, had an average score of 66.13, falling into the “fair” category, while the experimental class, which used the literature circle method, had an average score of 84.21, falling into the “good” category. The data analysis used in this study was the independent t-test, with the prerequisites of normality and homogeneity tests conducted first. The results obtained in this study showed that the significance value (2-tailed) was 0.001 < 0.05, which means there was a significant effect on the ability to write reviews of fictional works among eighth-grade students at SMP Muhammadiyah 01 Medan.